2002
DOI: 10.1046/j.1365-2036.2002.01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential intravenous/oral antibiotic vs. continuous intravenous antibiotic in the treatment of pyogenic liver abscess

Abstract: SUMMARYAim: Pyogenic liver abscesses result in substantial morbidity and mortality. Antimicrobial regimens using sequential intravenous=oral therapy may reduce the length of hospital stay. In this retrospective analysis, the efficacy of continuous intravenous antibiotic therapy (group I) vs. sequential intravenous=oral antibiotic therapy (group II) was studied in patients with pyogenic liver abscess. Methods: One hundred and twelve consecutive patients (55 in group I and 57 in group II) with pyogenic liver abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…19 Other investigations have reported to reduce both LOS and charges. For instance, treating pyogenic liver abscesses with sequential intravenous/oral antibiotics as opposed to treating them with continuous intravenous antibiotics reduced both LOS 20 Similarly, treating gram-positive infections with intravenous linezolid followed by oral administration was found to reduce the LOS and the associated cost of treatment when compared with intravenous or intramuscular teicoplanin. 21 Conversely, we found that although efforts to reduce the LOS associated with pyogenic arthritis have been successful, they have not resulted in decreased hospital charges.…”
Section: Discussionmentioning
confidence: 94%
“…19 Other investigations have reported to reduce both LOS and charges. For instance, treating pyogenic liver abscesses with sequential intravenous/oral antibiotics as opposed to treating them with continuous intravenous antibiotics reduced both LOS 20 Similarly, treating gram-positive infections with intravenous linezolid followed by oral administration was found to reduce the LOS and the associated cost of treatment when compared with intravenous or intramuscular teicoplanin. 21 Conversely, we found that although efforts to reduce the LOS associated with pyogenic arthritis have been successful, they have not resulted in decreased hospital charges.…”
Section: Discussionmentioning
confidence: 94%
“…One retrospective study found that transitioning to PO antibiotics decreased the cost of therapy and decreased the length of hospital stay for patients with pyogenic liver abscesses. 26 Key differences between our study and this one are that 80% of the patients had a single pyogenic liver abscess caused by Klebsiella pneumonia, and not all of the patients underwent drainage of their abscess. One prospective randomized controlled trial compared IV antibiotic therapy with sequential IV-to-PO antibiotic therapy in the treatment of complicated intraabdominal infections.…”
Section: Discussionmentioning
confidence: 60%
“…In adults, antibiotic therapy is recommended intravenously for at least 2 weeks and then orally for up to 6 weeks6, 7). In a recent report on PLA in adults, sequential intravenous therapy for 3 weeks followed by oral antibiotics for 3 weeks was safe and equally effective compared with 6-week intravenous antibiotic therapy10). According to another report in children, when percutaneous continuous drainage is maintained during 2 to 4 weeks, parenteral antibiotic therapy should also be maintained for at least 2 to 4 weeks, followed by oral antibiotics for a total of 4 to 6 weeks3).…”
Section: Discussionmentioning
confidence: 99%